2018
DOI: 10.1002/bjs.10805
|View full text |Cite
|
Sign up to set email alerts
|

Population-based cohort study of surgical myotomy and pneumatic dilatation as primary interventions for oesophageal achalasia

Abstract: Surgical myotomy was associated with a lower rate of reintervention and could be offered as primary treatment in patients with oesophageal achalasia who are fit for surgery. For those unfit for surgery, pneumatic dilatation may provide symptomatic relief with approximately 60 per cent of patients requiring reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In a case series, Yamaguchi et al (46) reported high dysphagia relief by 1-week therapy, but 50% of the patients relapsed at 3-24 months after treatment (Level 4; Grade: C). Due to the short-duration efficacy, authors usually propose BTX use only for achalasia patients unsuitable for more definitive procedure as a bridge therapy (Level 2b; Grade: B) (47)(48)(49)(50)(51). Some case reports suggested the use of BTX for achalasia during pregnancy (Level 4; Grade: C) (52)(53)(54).…”
Section: Botulinum Toxin Injectionmentioning
confidence: 99%
“…In a case series, Yamaguchi et al (46) reported high dysphagia relief by 1-week therapy, but 50% of the patients relapsed at 3-24 months after treatment (Level 4; Grade: C). Due to the short-duration efficacy, authors usually propose BTX use only for achalasia patients unsuitable for more definitive procedure as a bridge therapy (Level 2b; Grade: B) (47)(48)(49)(50)(51). Some case reports suggested the use of BTX for achalasia during pregnancy (Level 4; Grade: C) (52)(53)(54).…”
Section: Botulinum Toxin Injectionmentioning
confidence: 99%